2006
DOI: 10.1016/j.cardiores.2005.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Longer preservation of cardiac performance by sheet-shaped myoblast implantation in dilated cardiomyopathic hamsters

Abstract: Sheet-shaped myoblast graft implantation improved cardiac performance and prolonged life expectancy, associated with a reduction in myocardial fibrosis and re-organization of the cytoskeletal proteins in DCM hamsters. Thus, sheet-shaped autologous myoblast graft implantation may induce restoration of the heart in DCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(99 citation statements)
references
References 34 publications
1
97
0
Order By: Relevance
“…Similarly, skeletal myoblast grafts were able to improve left ventricular contraction, reduce fibrosis, and prevent remodeling via the recruitment of hematopoietic stem cells through the release of various growth factors [14]. The implantation of myoblast grafts also induced the restoration of left ventricular dilatation and prolonged life expectancy in dilated cardiomyopathic hamster [15]. Additionally, mesenchymal stem cell grafts demonstrated improved cardiac function in impaired rat hearts, with the reversal of cardiac wall thinning and prolonged survival after myocardial infarction.…”
Section: Cell Sheet Transplantation In Small Animal Modelsmentioning
confidence: 98%
“…Similarly, skeletal myoblast grafts were able to improve left ventricular contraction, reduce fibrosis, and prevent remodeling via the recruitment of hematopoietic stem cells through the release of various growth factors [14]. The implantation of myoblast grafts also induced the restoration of left ventricular dilatation and prolonged life expectancy in dilated cardiomyopathic hamster [15]. Additionally, mesenchymal stem cell grafts demonstrated improved cardiac function in impaired rat hearts, with the reversal of cardiac wall thinning and prolonged survival after myocardial infarction.…”
Section: Cell Sheet Transplantation In Small Animal Modelsmentioning
confidence: 98%
“…As mentioned above, scaffold-free engineered tissues are favorable to be transplanted for myocardial regeneration. We have demonstrated the therapeutic effectiveness of the cell sheets created from cardiomyocytes , myoblasts (Hata et al, 2006;Kondoh et al, 2006;Memon et al, 2005), and cardiac progenitor cells (Matsuura et al, 2009). We also started the clinical study of myoblast-sheet transplantation for DCM patients.…”
Section: Cell-sheet Engineeringmentioning
confidence: 99%
“…As the alternative to heart transplantation, regenerative medicine based on cell transplantation attracts increasing attention. Recent studies revealed that bone marrow-derived cells (Messina et al, 2004;Wollert et al, 2004), endothelial progenitor cells (Kawamoto et al, 2001), adipose-derived cells (Wang et al, 2009), and myoblasts Hata et al, 2006;Kondoh et al, 2006) have the potential to improve cardiac function when they are transplanted into a failing heart. Because these somatic cells can be harvested from the patients themselves, their clinical applications have already started.…”
Section: Introductionmentioning
confidence: 99%
“…Sekiya et al showed that the therapeutic effect reached a plateau at a quintuplet-layered cell sheet, because of the insufficient supply of oxygen and nutrition for skeletal myoblasts within thicker cell sheet constructs [70]. Kondoh et al showed that the transplantation of skeletal myoblast sheets improved a cardiac performance and prolonged the life span of animals, associating with the reorganization of the cytoskeletal proteins of host cardiac tissue and the reduction of myocardial fibrosis, using a dilated cardiomyopathy hamster model [71]. The significant therapeutic effects by the transplantation of autologous skeletal myoblast sheets were also confirmed in large-animal modes (a pacing-induced canine dilated cardiomyopathy heart failure model and a porcine ischemic myocardium model) [72,73].…”
Section: Three-dimensional Tissues Fabricated By Using Autologous Celmentioning
confidence: 99%